MARC 21 ձեվաչափ. ոչ գրքային հրատարակությունների արդի խնդիրներ - Հարությունյան Արմինե / Harutyunyan Armine (Հայաստանի ազգային գրադարան / National Library of Armenia, 2024)
Thus, the article presents a comprehensive overview of information on the non-book publications of the National Library of Armenia (NLA), including their processing, availability, and the types of non-book materials preserved, as well as electronic resources, both computer and non-computer files. The most important and mandatory fields for non-book publications in the MARC format are also presented. In conclusion, it can be observed that the entry of non-book publications in electronic format presents challenges for a number of libraries. However, article demonstrates the capabilities of the MARC format for non-book publications, detailing the relevant fields and record types.
Բանբեր Հայաստանի գրադարանների ։ Գիտամեթոդական էլեկտրոնային հանդես / Գլխավոր խմբագիր` Աննա Չուլյան ; Պատասխանատու խմբագիր՝ Հայկանուշ Ղազարյան ․- Երևան ։ «Գիրք» հրատարակչություն , 2024 ․- N 2 .- էջ 126 - 133
Keywords: Գրադարանագիտություն, մատենագիտություն և արխիվավարություն